Understanding the long-lasting attraction of malaria mosquitoes to odor baits. - Collins K Mweresa; Bruno Otieno; Philemon Omusula; Berhane T Weldegergis; Niels O Verhulst; Marcel Dicke; Joop J A van Loon; Willem Takken; Wolfgang R Mukabana (PLoS ONE, 2015)
The use of odor baits for surveillance and control of malaria mosquitoes requires robust dispensing tools. In this study, the residual activity of a synthetic mosquito attractant blend dispensed from nylon or low density polyethylene (LDPE) sachets was evaluated at weekly intervals for one year without re-impregnation. The potential role of bacteria in modulating the attraction of mosquitoes to odor-treated nylon that had been used repeatedly over the one year study period, without re-impregnation, was also investigated. Significantly higher proportions of female Anopheles gambiae sensu stricto mosquitoes were consistently attracted to treated nylon strips than the other treatments, up to one year post-treatment. Additional volatile organic compounds and various bacterial populations were found on the treated nylon strips after one year of repeated use. The most abundant bacteria were Bacillus thuringiensis and Acinetobacter baumannii. Autoclaving of treated nylon strips prior to exposure had no effect on trap collections of laboratory-reared female An. Gambiae (P = 0.17) or wild female An. Gambiae sensu lato (P = 0.26) and Mansonia spp. (P = 0.17) mosquitoes. Trap catches of wild female An. Funestus (P < 0.001) and other anophelines (P < 0.007) were higher when treated strips had been autoclaved prior to deployment as opposed to when the treated nylon strips were not autoclaved. By contrast, wild female Culex mosquitoes were more strongly attracted to non-autoclaved compared to autoclaved treated nylon strips (P < 0.042). This study demonstrates the feasibility of using odor baits for sampling and surveillance of malaria as well as other mosquito vectors over prolonged periods of time. Preliminary evidence points towards the potential role of bacteria in sustaining prolonged use of nylon material for dispensing synthetic attractant odorants for host-seeking malaria and other mosquito vectors but further investigations are required.